Outcomes for Elderly Patients With Atypical Femoral Fractures Compared to Typical Femoral Fractures for Length of Stay, Discharge Destination, and 30-Day Mortality Rate - Davenport, Dominic (Geriatr Orthop Surg Rehabil, 2018)
INTRODUCTION: Despite increasing recognition of atypical femoral fractures (AFFs), there’s conflicting evidence about incidence, aetiology, and short-term outcomes of these injuries. This study reports the incidence of AFFs at our center and compares the early postoperative outcomes against typical femoral fractures (TFFs). METHODS: A retrospective observational cohort study of patients presenting to our trauma unit between November 2015 and July 2016 was undertaken. Inclusion criteria required radiologically confirmed proximal femoral fracture, which was then categorized as AFF or TFF. Primary outcome measures included length of stay, discharge destination, and 30-day mortality. RESULTS: Two hundred thirty-nine patients presented to our trauma unit over 9 months with either a fractured neck of femur or proximal femoral fracture. A total of 122 were identified as pertrochanteric, subtrochanteric, or proximal femoral shaft fractures of which 25 (20.5%) displayed atypical radiographic features consistent with AFF. The 2 groups were similar for average age (TFF 85.3 years vs AFF 85.0 years), gender (19% vs 16% male gender), American Society of Anaesthesiology grade (3.0 vs 3.0), cognitive score (abbreviated mental test score = 7.03 vs 7.08), and preinjury place of residence (88.9% vs 92.0% lived in own home). Typical fractures were fixed with either dynamic hip screw or intramedullary nailing, all atypical fractures were fixed with intramedullary nailing. There was no statistical difference between the 2 groups for length of stay (12.8 days vs 14.3 days; P > .05), discharge to preinjury residence (45.1% vs 36%; P > .05), or 30-day mortality (8.1% vs 12%; P > .05). DISCUSSION: In our predominantly geriatric population atypical radiographic features were observed in around 10% of patients presenting with proximal femoral fractures or fractured neck of femur. Previous studies have reported poor outcomes for pain, mobility, and length of stay after AFF. However, we observed no difference in short-term outcome measures when compared to patients with typical proximal femoral fracture patterns at our trauma unit. CONCLUSION: With modern principles of trauma care outcomes achieved following AFFs may be equivalent to typical femoral fractures in the geriatric population.